Metode Kangguru, BBLR, Hubungan Perawatan Metode Kangguru pada Bayi Brat Badan Lahir Rendah dengan Peningkatan SPO2 di Ruang Neonatais RSUD Sumberejo: THE RELATIONSHIP BETWEEN THE KANGAROO CARE METHOD IN LOW BIRTH WEIGHT INFANTS AND THE INCREASED SPO2 - Wulandari, Endah Sri (WELL BEING, 2024)
Background: Low birth weight infants are susceptible to apnea, a pathological cessation of breathing that causes physiological changes such as decreased central stimulus, peripheral perfusion, cyanosis, bradycardia, and hypotonia, and requires treatment. To prevent apnea, one effective therapy is kangaroo care. The purpose of this study was to determine the frequency of apnea in low birth-weight infants before and after kangaroo care and to assess the effect of kangaroo care on the frequency of apnea in the Neonatal Unit of RSUD Sumberejo Bojonegoro. Methods: The study design was a pre-experimental One Group Pre-Test - Post-Test design. The sample consisted of infants with a birth weight of less than 2500 grams. The instruments used were kangaroo care implementation sheets and an oximeter. Bivariate analysis using Spearman's rho test. Results: The result of analysis with SPSS 25 showed a significance value of p = 0.001 < 0.05, indicating that kangaroo care affects the frequency of apnea in low-birth-weight infants. Conclusion: This study concludes that kangaroo care impacts the frequency of apnea in low birth-weight infants. The recommendation is to make kangaroo care routine for low birth-weight infants.